The comparison of readability between information texts from web sites of private clinics and private hospitals (Annals of Medical Research, 2021)
Aim: Rhinoplasty is a surgery which can be done in state hospitals, private hospitals and private clinics. Patients gen-erally go to the most suitable clinic whereas most surgeons prefer to perform surgery in private clinics. Thus, patients often confuse where to attend. Social media plays a crucial role for patients to decide where and who to choose. We compared readability of the information text from internet pages of private clinics and private hos-pitals from both plastic surgeons and otorhinolaryngologists.Material and Methods: The word “Rhinoplasty” was searched through internet and first 30 web sites were taken into account. First 100 words from information texts about rhinoplasty from both private clinic and hospital web sites were copied and studied using a program called LIDA. Gunnig-Fog index, Flesch-Kincaid and Atesman values were noted and evaluated.Results: The readability of both private hospitals and private clinics were found to be hard. Flesch-Kincaid values showed that information texts from private clinics in web sites (23.24 ± 3.45) were significantly different (p=0,035) than private hospitals (25,19 ± 3,5). As believed to be more specific to Turkish, Atesman values in private clinics (48,58 ± 16,71) were found to be more readable than private hospitals (38.81 ± 18.06) (p=0,034).Conclusion: Comparison of information texts between private clinics and private hospitals of plastic surgeons and otorhino-laryngologists showed that Atesman values, which are believed to be more specific to Turkish, and Flesch-Kincaid values were significantly high in private clinics suggesting it is easier to understand. To sum it up, infor-mation texts guide patients to private critics.
Keywords: Internet; otorhinolaryngologic surgical procedures; otorhinolaryngologic diseases; communication; private clin-ic; private hospital; rhinoplasty.